Deployment of performance indicators toward bridging monitoring gaps in Africa’s Great Green Wall - Abdullahi Mohammad Jalam; Amir Hamzah Sharaai; Mariani Ariffin; Norzalina Zainudin; Haruna Danladi Musa (Environmental Health Engineering and Management, 2023)
Background: The health and productivity of the land across the Sahel are in declension due to desertification. This has lowered the quality of ecosystem services and has led to a vicious cycle of drought, famine, poverty, and insecurity in the region. As one of the flagship interventions of the UN’s decade (2020-2030) of ecosystem restoration to tackle desertification and respond to climate change, there are mixed reactions to the successes of the Great Green Wall (GGW) in Nigeria due to the failure of the Sustainability of Policy Instrument. Methods: A two-round Delphi reached consensus on 42 sub-indicators under 14 indicators as indicated by Kendell’s (W = 0.509, P = 0.001) and high correlation between rounds (rho = 0.959, P = 0.001). The indicators were then deployed to assess the GGW in a questionnaire (n = 401) via a multi-stage sampling, and their performance was weighted using principal component analysis (PCA). Results: “Proportion of land reclaimed” was recorded as the highest-performing indicator due to the multifaceted afforestation program covering fodder and wood lot areas, while “dune fixation” has the least performance due to the lack of employment of ecological engineering tools. The findings showed that the presence of local jobs is not significant in raising the livelihood status above the poverty line. Conclusion: To meet the 2030 timeline, there is a need to scale up the implementation of the GGW and support the desert frontline states (DFS) with alternative energy to reduce the rate of deforestation.